(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the impact of an educational intervention on self-care and Quality of Life (QL) of patients with decompensated Heart Failure (HF) after hospital discharge. This is part of a Randomized Clinical Trial, whose sample was divided into Intervention Group (IG) and Control Group (CG). The IG was monitored and guided by nurses in person and over the phone, with a physical examination, application of questionnaires (QL and self-care) and therapeutic guidance. Both groups were evaluated on the 60th day after discharge. Data were analyzed using the Statistical Package for Social Sciences tool, version 21.0. Of the 22 patients evaluated, 15 were from the CG and 7 from the IG. The IG had better scores compared to the CG regarding self-care (100% vs 47%, p=0.02) and QoL (44% vs 20%, p=0.36). The nursing intervention performed is presented as a feasible strategy to improve self-care and quality of life for patients with HF.